LOCAL GOVERNMENT CAPACITY IN IMPLEMENTING SINGLE-USE PLASTIC BAN POLICY IN BALI PROVINCE - Ida Bagus Perdana Kumara; Eko Supeno; Bintoro Wardiyanto (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Inorganic waste, especially single-use plastic, has a negative impact on the environment and society. The trend of increasing plastic production is not followed by the ability to manage waste properly. As a result, there is a buildup of waste in the world. Indonesia is one of the countries with the highest plastic waste problem. The problem of plastic waste can harm a country such as decline in the tourism sector. Bali Province is one of the provinces with tourism potential. Plastic waste is also a problem there. Several international media such as Time and BBC have reported about this situation. In response to this problem, the local government published Peraturan Gubernur Bali Nomor 97 Tahun 2018 which prohibits the use of three types of single-use plastic, namely plastic bags, styrofoam, and straws. In its implementation, there is problem in public compliance, can find people use single plastic easily. This research contributes the analysis of local government capacity in implementing the policy. As a result, local governments are lacking in monitoring and sanctioning, causing a decrease in community compliance. However, they are strong enough in explaining the concept and causality relationship to achieve the goal.